Alternative methods of reducing government expenditure - Roland Vaubel (Intereconomics, 1981)
In recent years spectacular attempts by various major industrialized countries to reduce government expenditure have met with limited success and given rise to heavy controversies. What are the lessons to be learnt? What are the principles to be followed in cutting government expenditure?
Keywords: 330; Industrialized Countries